Giving Medical Rehabilitation Discretion to Children Perpetrators of Drug Abuse - Yudhisthira; Hasanal Mulkan (IHSA Institute, 2022)
Drug trafficking is a universal social phenomenon (a universal social phenomenon) in human life, and is even said to have become the oldest social problem of human kind. With the discretionary authority that is owned, it is understandable if a legal issue does not have to be resolved through the courts, but the resolution can be submitted to the decision of the police, in connection with the discretion against drug and psychotopic abuse, the police can also exercise discretion, especially against the perpetrators who are still children, discretion towards children abusing narcotics and psychotropic substances. As for the formulation of the problem in writing the journal, namely the reason for the police in providing medical rehabilitation descriptions for children who are perpetrators of drug crimes,